If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -3.6 = 1.6(x + -1) Reorder the terms: -3.6 + Y = 1.6(x + -1) Reorder the terms: -3.6 + Y = 1.6(-1 + x) -3.6 + Y = (-1 * 1.6 + x * 1.6) -3.6 + Y = (-1.6 + 1.6x) Solving -3.6 + Y = -1.6 + 1.6x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '3.6' to each side of the equation. -3.6 + 3.6 + Y = -1.6 + 3.6 + 1.6x Combine like terms: -3.6 + 3.6 = 0.0 0.0 + Y = -1.6 + 3.6 + 1.6x Y = -1.6 + 3.6 + 1.6x Combine like terms: -1.6 + 3.6 = 2 Y = 2 + 1.6x Simplifying Y = 2 + 1.6x
| 12x+42y=360 | | 5x^2+x+1=5 | | X+(x-6)= | | 10=5-4x | | 7j+8=78 | | 5(8+7)=5*x+5*7 | | (-7)+f=(-14) | | -5/8*s=-15 | | 5s+s-3=-10+2s-5 | | -5/8*t=-15 | | 9/3(4x6/8) | | (-2)=y+22 | | 4x+2x-3=-15-3+x | | 1/9-2/3x=3 | | 1/7/1/11=x/14 | | 2/5=40 | | -2x^2+4=-96 | | f+(-7)=3 | | -5/8P=-10 | | 24/22=x/77 | | (-10)+m=(-24) | | 3/4n=228 | | 5/x=25/20 | | 3m+30=81 | | 0.96=0.06(12+x) | | f(x)=2x+7x+12 | | x+(-9)=6 | | -1+-2d=-13 | | 5/9q=7/9 | | 8x^2+34x+24=1366 | | 28/5=140/x | | -73=7+8x |